2014
DOI: 10.1002/elps.201400449
|View full text |Cite
|
Sign up to set email alerts
|

On‐capillary derivatisation as an approach to enhancing sensitivity in capillary electrophoresis

Abstract: Separation technologies play an important role in revealing biological processes at various omic levels, in pharmacological and clinical research. In this context, CE is a strong candidate for analyses of samples with rapidly increasing complexity. Even though CE is well known for its many advantages in this regard, the sensitivity of CE analyses is insufficient for many applications. Accordingly, there are generally three main options for enhancing the sensitivity of CE analyses - using special detection tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 189 publications
1
30
0
Order By: Relevance
“…The automation of the derivatization process by the autosampler of the HPLC system evades the stability issue by putting the derivatization procedure directly before the analysis, reducing the time in which the derivatives have to be stable to a minimum. This has also been reported for the analysis of OPA derivatized AAs by capillary electrophoresis . OPA reacts within a few minutes in an aqueous borate buffer (pH = 10.0) in the presence of these thiols with primary AAs to give a fluorescent isoindole product (see Figure ).…”
Section: Introductionsupporting
confidence: 68%
“…The automation of the derivatization process by the autosampler of the HPLC system evades the stability issue by putting the derivatization procedure directly before the analysis, reducing the time in which the derivatives have to be stable to a minimum. This has also been reported for the analysis of OPA derivatized AAs by capillary electrophoresis . OPA reacts within a few minutes in an aqueous borate buffer (pH = 10.0) in the presence of these thiols with primary AAs to give a fluorescent isoindole product (see Figure ).…”
Section: Introductionsupporting
confidence: 68%
“…In-capillary derivatization emerges as a powerful technique as it involves low reagents and sample consumption which causes minimum sample dilution. Moreover, it offers high derivatization efficiency, and allows full automation of the derivatization process which often brings better repeatability and reproducibility as reported in a recently published review article [42]. Fradi et al reported a work regarding the enantioseparation of 15 amino acids in an MEKC-UV system using (-)-1-(9-fluorenyl)ethyl chloroformate as chiral labeling reagent [35].…”
Section: On-line Sample Treatment Techniquesmentioning
confidence: 99%
“…However, there were specific reviews published about the importance of derivatisation in CE for the analysis of natural products , biogenic amines in food samples , proteomics , microfluidic chip electrophoresis , peptides , herbicides and chiral amino acids . Also, a recent and comprehensive review about in‐capillary derivatisation was given by Glatz .…”
Section: Introductionmentioning
confidence: 99%